Reassessing the relationship between the financial sector and economic growth: Dynamic panel evidence - Alexiou, Constantinos; Vogiazas, Sofoklis; Nellis, Joseph G. (Wiley, 2018)
Historically, the development of the financial sector has been an indispensable driver of economic growth. In the aftermath of the Great Recession, there is a pressing need to reassess the role of the financial sector in the determination of economic growth. Using a dynamic panel framework, our analysis covers 34 European and Commonwealth of Independent States economies for the period 1998–2014 and controls for the role of macroeconomic and institutional variables. Our evidence suggests that the potential benefits of the financial sector finance may have dramatically reversed in recent years, resulting in “un-creative destruction.” The results suggest, tentatively, that there has been a severance of the link between the financial sector and the real economy. The results, however, vary according to the level of economic development across the European and Commonwealth of Independent States economies. In the case of developing market economies, the financial intermediation proxies are not significant in explaining economic growth. The effect of changes in investment expenditure, the money supply, wages, unit labour costs, and trade openness is found to be strong and in line with a priori expectations across all country samples. Notably, government consumption is also found to be a significant driver of economic growth, except in the developing market economies in the period following the Great Recession. In line with the growing consensus in other research areas, we provide evidence of a robust role for the institutional framework proxied by the quality of governance in determining economic development.
Keywords: CIS; Economic growth; European economies; Financial sector